2022
DOI: 10.1556/2006.2022.00024
|View full text |Cite
|
Sign up to set email alerts
|

Involvement in Sexaholics Anonymous and life satisfaction: The mediating role of meaning in life and hope

Abstract: Background and aims Some people are preoccupied with their sexual urges and fantasies and lose control over their sexual behaviors, which can cause adverse consequences for their health and well-being. One of the options available for individuals seeking treatment for compulsive sexual behavior disorder (CSBD) is a self-help group based on the twelve-step program. The main purpose of the current study was to examine the direct and indirect (through meaning in life and hope) relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…The specificity of a sample may be a moderator in this relationship. For example, in a sample of Sexaholics Anonymous from Poland, the search for meaning was negatively related to life satisfaction ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of a sample may be a moderator in this relationship. For example, in a sample of Sexaholics Anonymous from Poland, the search for meaning was negatively related to life satisfaction ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study asserted that search for meaning in life would either predict increased suicidal ideation or be irrelevant to it (Kleiman & Beaver, 2013 ). It seems reasonable that search for meaning in life is positively related to greater depression symptom severity and lower happiness and life satisfaction (Park, 2010 ; Wnuk & Charzynska, 2022 ), and also positively related to negative psychological constructs like rumination and a feeling of a lack of personal growth (Steger et al, 2008 ). One study found that search for meaning in life is unrelated to suicidal ideation (Lew et al, 2019 ), while another reported that relationships between search for meaning in life and mental health depended on personal life events (Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A1, positive affect; A2, negative affect; M1, presence of meaning in life; M2, search for meaning in life; S1, pessimism; S2, sleep; S3, despair for meaning in life would either predict increased suicidal ideation or be irrelevant to it (Kleiman & Beaver, 2013). It seems reasonable that search for meaning in life is positively related to greater depression symptom severity and lower happiness and life satisfaction (Park, 2010;Wnuk & Charzynska, 2022), and also positively related to negative psychological constructs like rumination and a feeling of a lack of personal growth (Steger et al,Fig. 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This conflict might explain his lifestyle. Indeed, people with meaning in life drink less alcohol (Copeland et al, 2020) and are more likely to be part of support groups for Sexaholics (Wnuk and Charzyńska, 2022). Instead, adults who still look for meaning in life often shown unhealthy drinking behavior (Copeland et al, 2020).…”
Section: Discussionmentioning
confidence: 99%